FORMATION AND DEVELOPMENT OF SLOPES OF VOLCANIC STRUCTURES OF THE ARMENIAN HIGHLANDS (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
The article identifies the features of the volcanic slopes of the Armenian Highlands, taking into account the fact that their formation and development occurred under conditions of relative moisture deficiency (with the exception of the high-mountain belt). The latter are rather poorly sanctified in the scientific literature, so the author's research to some extent fills the existing gap. The volcanic relief with the corresponding slopes was formed here mainly in the Pliocene-Quaternary period and belongs to the so-called Armenian volcanic Highlands. The formation and development of the volcanic slopes of the highlands has a number of features: relative youth; their rapid formation, which is many times faster than the rate of weathering of volcanogenic rocks; the composition of rocks (lava, pyroclastic material), which is essential in the formation of a slope of a certain morphology; water permeability of volcanogenic rocks; intermediate denudation basis for most volcanic slopes. The slope cover on most volcanic slopes of the highlands as a whole is at the initial stage of formation. The basal horizon prevails mainly and the morphodynamic horizon is less common. The cover horizon is found mainly in the lower, more gentle part of the slope. In the highlands, a parallel retreat of the slopes without significant flattening is noted at the edges of lava flows and plateaus, which directly break off to the riverbed, and the latter manages to remove the collapsed material. Parallel retreat in this case is facilitated by the presence of columnar separations in the lavas.
Keywords: Armenian volcanic highlands; parallel retreat of slopes; slope cover